The Emergence and Effects of Culturally Congruent Leadership: Current Status and Future Developments - Ghulam Mustafa; Rune Lines (Entrepreneurial Business and Economics Review)
Objective: The purpose of this paper is to provide a critical assessment of the cross-cultural leadership literature and suggest avenues for future developments on both empirical and conceptual fronts.